2006
DOI: 10.1007/s10734-004-6391-8
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Practical Training in Linking Theoretical Studies with Practice

Abstract: Today's experts must continuously reconstruct their expertise and be able to apply their theoretical knowledge in actual work. The development of expertise is a long process, during which theoretical, practical and metacognitive elements of expert knowledge are integrated into a coherent whole. It is important to foster student's learning and integration of theoretical knowledge in practice during tertiary education. One tool for this is to pay more attention to practical knowledge in the theoretical part of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 36 publications
2
74
0
1
Order By: Relevance
“…As for educational knowledge adoption, educational researchers prefer more on theoretical knowledge, while educational parishioners propose to combine them (Samo Pavlin et al, 2010). Besides, knowledge acquirement is one step to form expertise for future use, universities need to further design mechanisms to motivate the students to combine scattered knowledge together (Nina Katajavuori et al, 2006). Even more, some scholars divide a given course into theoretical and practical components to suit for the course function, in order to meet the student demand in various knowledge structure (Karl Maton, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As for educational knowledge adoption, educational researchers prefer more on theoretical knowledge, while educational parishioners propose to combine them (Samo Pavlin et al, 2010). Besides, knowledge acquirement is one step to form expertise for future use, universities need to further design mechanisms to motivate the students to combine scattered knowledge together (Nina Katajavuori et al, 2006). Even more, some scholars divide a given course into theoretical and practical components to suit for the course function, in order to meet the student demand in various knowledge structure (Karl Maton, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The semi-structured questionnaire is designed with the reference to Robert K. Tener (1996), Bolivar A. Senior (1998), Eraut (2000), Nina Katajavuori et al(2006), etc.. all interviews are required to give their judgment within questionnaire, and describe their experience in scoped titles. The whole interview process is recorded by audio recorders.…”
Section: <Figure 1 About Here>mentioning
confidence: 99%
“…[18][19][20][21] Studies showed that students found the previous curriculum fragmented and considered the theoretical studies challenging. Trends of surface-level learning also were demonstrated which was manifested in fact memorizing and difficulties knowledge application by the students.…”
Section: Evaluation Of Teaching and Learningmentioning
confidence: 99%
“…21 However, the quality of precepting in different pharmacies was reported to vary. 20 An international evaluation panel also suggested that the 6-month experiential training should be utilized in the curriculum more effectively.…”
Section: Evaluation Of Teaching and Learningmentioning
confidence: 99%
See 1 more Smart Citation